THE CRITICAL ROLE OF KNOWLEDGE SHARING ACTIVITY AND INTERGENERATIONAL CONFLICT SOLUTION TO CREATE FAMILY BUSINESS SUSTAINABILITY: INTERGENERATION RELATIONSHIP QUALITY AS MODERATING - Liliana Dewi; Elia Ardyan (International Journal of Accounting, Finance and Business, 2020)
This study aims to examine the important role of knowledge sharing activities and intergeneration solutions in order to create family business sustainability. This research also examines the moderating impact of intergeneration relationship quality. Respondents in this study were 213 business owners of Batik SMEs in Central Java. Respondents are from generation 2-4 of the family business. Data were analysed using SEM-PLS. The results of this study indicate that knowledge sharing activities and intergeneration conflict solutions are able to create family business sustainability. This research also found that a quality relationship between parent and child is able to moderate the influence of knowledge sharing activity and intergeneration conflict solution. This study contributes to theoretical and managerial contributions regarding sustaining family businesses.